PENGARUH MODEL PEMBELAJARAN PROBLEM-BASED INSTRUCTION TERHADAP HASIL BELAJAR SISWA PADA TEMA DAERAH TEMPAT TINGGALKU DI KELAS IV SDN 094114 MARDINGDING PEMATANG RAYA - Romauli Manalu; Rumiris Lumban Gaol; Darinda Sofia Tanjung (Jurnal PAJAR (Pendidikan dan Pengajaran), 2022)
This experimental research aims to examine the effect of Problem-Based Instruction (PBI) as a learning model on the learning outcomes of fourth-grade students at SD Negeri 094114 Mardingding Pamatang Silimahuta, Pematang Raya, in the 2020/2021 academic year. The study involved 30 students in a single experimental class, using a descriptive method. Data were collected through multiple-choice tests, and hypothesis testing was conducted using a t-test. The results showed that students’ learning outcomes under the PBI model were classified as very good, with an average score of 86.46. Furthermore, correlation analysis indicated a significant positive relationship between the application of PBI and students’ learning outcomes, with a correlation coefficient of rhitung=0.761>rtable=0.361r_{\text{hitung}} = 0.761 > r_{\text{table}} = 0.361rhitung​=0.761>rtable​=0.361. These findings demonstrate that the Problem-Based Instruction model has a significant positive effect on the learning outcomes of fourth-grade students.